2003
DOI: 10.1139/l02-080
|View full text |Cite
|
Sign up to set email alerts
|

Static ice loads on dams

Abstract: A 9 year field program was undertaken from 1991–1992 to 1999–2000 to (i) measure the loads in the ice sheet near a dam, (ii) measure the load distribution between a gate and a pier, and (iii) compare the loads on wooden and steel stoplogs. Parallel work was conducted to develop analytical predictors for ice loads. Much progress has been made. One of the most significant findings has been to identify the importance of water level changes on the resulting ice loads. Ice loads are much higher and more variable (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Changes in ice conditions can affect hydroelectric operations in a number of ways, both positively and negatively. For example, the estimation of ice loads on facilities such as dams, intakes, outlets, and gates is important both for engineering design and operations (Comfort et al 2003). A shorter ice season and thinner ice cover could reduce the static ice loads on dams, but on the other hand, a more unstable winter with mechanical ice break-ups could increase the dynamic loads on in-channel facilities.…”
Section: Hydroelectric Powermentioning
confidence: 99%
“…Changes in ice conditions can affect hydroelectric operations in a number of ways, both positively and negatively. For example, the estimation of ice loads on facilities such as dams, intakes, outlets, and gates is important both for engineering design and operations (Comfort et al 2003). A shorter ice season and thinner ice cover could reduce the static ice loads on dams, but on the other hand, a more unstable winter with mechanical ice break-ups could increase the dynamic loads on in-channel facilities.…”
Section: Hydroelectric Powermentioning
confidence: 99%
“…Pressures in ice cover were measured with D r a f t 6 6 two BP sensor groups (Duckworth and Westermann 1989) at about m from the dam face (considered to be "far field" -FF). Comfort et al (2003) reported that the loads resulted from superposition of: (i) large ice temperature changes produced by very cold winter; and (ii) intermediate water level fluctuations (an especially important contributor). The thermal strain rate at the time of peak load was ~10 -9 s -1 .…”
Section: Multi-day Event (Seven Sisters Mb)mentioning
confidence: 99%
“…Based on a nine-year field program at nine sites, Comfort et al (2003) found that thermal ice loads can be amplified by intermediate water level fluctuations (of about an amount equal to the ice thicknessh. Here and further, definitions of symbols and abbreviations are given in the Table 6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations